Digestibility and gastrointestinal transit of Ulva fasciata seaweed meal in tilapia (Oreochromis niloticus) juveniles: basis for the inclusion of a sustainable ingredient in aquafeeds (Research, Society and Development, 2020)
The seaweed Ulva fasciata has many features favorable to integrated multi-trophic aquaculture (IMTA). It is efficient at biofiltering, shows high biomass production, and is rich in many nutrients useful in aquatic animal diets. We evaluated the digestibility of the seaweed meal of U. fasciata produced in IMTA and its effects on gastrointestinal transit time in tilapia (Oreochromis niloticus) juveniles. Juveniles (6.30 ± 1.80 g initial weight, and 5.5 ± 0.61 cm initial length) were cultivated in six tanks (50 individuals per tank) in a closed recirculating aquaculture system. The digestibility of Ulva meal was 57.92 ± 5.21% for dry material, 78.59 ± 1.91% for protein, and 69.87 ± 3.72% for energy. The inclusion of 10% seaweed meal did not alter the gastrointestinal transit time in tilapia juveniles as compared to controls. The earliest colored feces were observed four hours after first feeding in both treatments (feed diets with [10%] and without seaweed); all fecal material was colored after ten hours. The digestibility of seaweed meal was satisfactory for dry material, protein, and gross energy, and the inclusion of 10% of that meal did not change gastrointestinal transit time - indicating that the inclusion of 10% seaweed meal in tilapia diet is safe and without any nutritional use losses.